Frustrated Lewis pairs derived from xanthene and related backbones - Zulkifly, IAB (2020)
This thesis examines the synthesis and the reactivity of both novel and previously reported intramolecular dimethylxanthene, dimethylthioxanthene and acridan derived frustrated Lewis pairs (FLPs). Moreover, it also reports on novel acridan-based Lewis bases and acids, and the subsequent reactivity of such species within intermolecular FLPs